Cognitive impairment predicts disability progression and cortical thinning in MS: An 8-year study. (May 2017) - Pitteri, Marco; Romualdi, Chiara; Magliozzi, Roberta; Monaco, Salvatore; Calabrese, Massimiliano
Background: Multiple sclerosis (MS) is a chronic immune-mediated disease of the central nervous system (CNS). Although cognitive impairment (CI) affects a large proportion of MS patients, only few data are available about its prognostic value associated with advanced magnetic resonance imaging (MRI) metrics. Objectives: We aimed at investigating the relationship between the early CI and the disease progression over 8-year follow-up in MS patients. Methods: We conducted a retrospective 8-year longitudinal study involving 78 patients with relapsing-remitting MS, who completed neuropsychological examination and structural MRI at the time of diagnosis. Each patient was clinically evaluated every 6 months, and cortical thickness was quantified at baseline and at the end of the follow-up. Patients were classified as having normal cognition and mild or severe CI. Results: The results show that CI at the time of diagnosis is a good predictor of conversion to definite MS ( p < 0.001), disability progression ( p < 0.001), as well as of transition to secondary progressive phase ( p < 0.001) and of cortical thinning ( p < 0.001). Conclusion: We confirmed and extended the evidence that early CI might be helpful in the identification of MS patients at high risk of disability progression and poor clinical outcome and should be considered as a marker of most aggressive pathology.